Correlation Between Clinical Signs and High-resolution Manometry Data in Children. Issue 5 (May 2019) - Juzaud, Marine; Lamblin, Marie-Dominique; Fabre, Alexandre; Alessandrini, Marine; Baumstarck, Karine; Bazin, Camille; Esteve, Clothilde; Laborde, Nolwenn; Osei, Lindsay; Michaud, Laurent; Gottrand, Frederic; Vitton, Veronique
ABSTRACT: Objectives: High-resolution manometry (HRM) is the gold standard for diagnosis of esophageal motility disorders. However, clinical signs associated with these disorders are nonspecific, and it is difficult to correlate clinical signs with HRM data. The main objective of our study was to assess the positive predictive value (PPV) and negative predictive value (NPV) of each clinical sign, as well as their sensitivity and specificity in the diagnosis of esophageal motility disorders. Methods: This is a bicentric retrospective cohort study based on HRM data collected between May 2012 and May 2016. The studied symptoms were weight loss, feeding difficulties, swallowing disorders, dysphagia, food blockages, vomiting, gastroesophageal reflux disease (GERD), belching, and respiratory symptoms. HRM data were analyzed according to the Chicago Classification (3.0). Results: In total, 271 HRM data were analyzed, of which 90.4% showed abnormal results. HRM was well tolerated in 91% of the cases. The most common esophageal motility disorder was ineffective esophageal motility (38%). Weight loss was significantly associated ( P  = 0.003) with an abnormal HRM with a 96% PPV. Conclusions: With nonspecific clinical signs suggesting an esophageal motility disorder, weight loss was a predictive sign of abnormal HRM results. HRM was well tolerated in pediatric patients, and ineffective esophageal motility appears to be the most frequent motility disorder in our cohort, as already observed in adult patient studies. Abstract : Supplemental Digital Content is available in the text